2016
DOI: 10.31051/1852.8023.v7.n2.14176
|View full text |Cite
|
Sign up to set email alerts
|

DOUBLE TRANSVERSE FORAMEN IN INFANTILE CERVICAL VERTEBRAE OF THE LATE 17TH AND EARLY 18TH CENTURIES. Doble foramen transverso en las vértebras infantiles cervicales de finales del siglo XVII y principios del XVIII

Abstract: La presencia de doble foramen transverso es una variante anatómica que se observa con frecuencia en el raquis cervical inferior y que presenta implicaciones clínicas en relación con la arteria vertebral. Aunque en la actualidad existe cierta controversia acerca de si el origen de esta variante cervical es congénito o adquirido, y a pesar de que la presencia de doble foramen transverso en población infantil descartaría un origen degenerativo-artrósico, se encuentra una falta de información acerca de su presenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…In addition, the recent study showed significantly higher AP diameters of C6-7 and T diameter of only C7 in male, indicating that such parameters could be used to be very helpful in forensic identification of complete cervical vertebral FT remains. These findings were similar to those of previous reports in Korean (Malla et al, 2018) and Spanish populations (Quiles-Guiñau et al, 2017) but differed in that the C5 T diameter in females in our study was significantly longer than in the males. Consideration of lateral size differences may help prevent left vertebral neurovascular damage during spinal surgery.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the recent study showed significantly higher AP diameters of C6-7 and T diameter of only C7 in male, indicating that such parameters could be used to be very helpful in forensic identification of complete cervical vertebral FT remains. These findings were similar to those of previous reports in Korean (Malla et al, 2018) and Spanish populations (Quiles-Guiñau et al, 2017) but differed in that the C5 T diameter in females in our study was significantly longer than in the males. Consideration of lateral size differences may help prevent left vertebral neurovascular damage during spinal surgery.…”
Section: Discussionsupporting
confidence: 92%
“…FT variation is clinically significant to radiologists and surgeons planning posterior operations at the lower cervical spine (C3-C7). The morphometry (such as type and diameter) and rates of variance of FT have been found to differ by population, with previous studies being conducted in Israel, Japan, China, India, Italy, Turkey, the US, Greece, Spain, Chile, South Africa, and Korea (Taitz et al 1978;Kimura et al, 1985;Sangari et al, 2015;Zibis et al, 2016;Quiles-Guiñau et al, 2017;Guerra et al, 2017;Abdul et al, 2018;Malla et al, 2018;Gupta & Agarwal, 2019). Ours was the first study to report the incidence of variance and morphometric features of the lower cervical spine FT in a Thai population.…”
Section: Discussionmentioning
confidence: 73%
“…This was later confirmed by Bodon et al (2016) who also described anastomotic veins connecting the venous sinuses superiorly (suboccipital cavernous sinus) and inferiorly (vertebral artery venous plexus) on the posterior arch of the atlas (Arnautović et al, 1997). In addition to describing the anastomotic vein, both Paraskevas et al (2005) and Karau et al (2010) detected a supplementary occipital nerve in the RTF (Kaushal, 2011; Quiles‐Guiñau et al, 2016). Other researchers, including Dubreuil‐Chambardel (1921) noticed an additional slender artery (Gupta et al, 1979) and Sylla (1976) hypothesized that a dorsal branch of the first cervical spinal nerve runs through the RTF.…”
Section: Discussionmentioning
confidence: 99%
“…An RTF should not be considered as a mere anatomical idiosyncrasy, but as an anatomical variant of the atlas with significant clinical correlations and implications. Paraskevas et al (2005) found a high incidence of a coexisting canal for the vertebral artery (CVA) and a complete RTF (72.22%) (Quiles‐Guiñau et al, 2016). This can potentially lead to compression of the vertebral veins, ultimately causing vertebrobasilar insufficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation